2015
DOI: 10.4269/ajtmh.14-0420
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Antibody Responses in Local and Immigrant Residents of Areas with Autochthonous Malaria Transmission in Greece

Abstract: Abstract. Greece has been officially malaria free since 1974. However, from 2009 to 2012, several locally acquired, cases of Plasmodium vivax malaria were detected, in immigrants and in Greek citizens. In this study, the antibody (Ab) response of Greeks and immigrants with documented malaria was initially assessed, followed by an Ab screening of Greeks and immigrant residents of local transmission areas. Of the 38 patients tested, 10.5% of Greeks and 15.7% of immigrants were positive 5-7 months after infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…Taking into consideration that underreporting is very likely, we assume that a significant percentage of the Pakistani migrants have been exposed to P. vivax since childhood and are carriers of P. vivax hypnozoites, while their relapses can be asymptomatic or minimally symptomatic as is indicated from our results and other related studies [30][31][32][33][34]. Detection of hypnozoites through a biological method is currently not possible, and serology is not widely accepted as a potential diagnostic method of infection, while it is difficult to implement systematically [35,36]. In addition to the above, further barriers due to documentation status, low risk perception of malaria and language barriers discourage these migrants from accessing health care services promptly.…”
Section: Discussionmentioning
confidence: 78%
“…Taking into consideration that underreporting is very likely, we assume that a significant percentage of the Pakistani migrants have been exposed to P. vivax since childhood and are carriers of P. vivax hypnozoites, while their relapses can be asymptomatic or minimally symptomatic as is indicated from our results and other related studies [30][31][32][33][34]. Detection of hypnozoites through a biological method is currently not possible, and serology is not widely accepted as a potential diagnostic method of infection, while it is difficult to implement systematically [35,36]. In addition to the above, further barriers due to documentation status, low risk perception of malaria and language barriers discourage these migrants from accessing health care services promptly.…”
Section: Discussionmentioning
confidence: 78%
“…Another study utilised serology to determine geographical ‘pockets’ of seropositivity but did not report seroprevalence estimates for these pockets [ 47 ]. Seroprevalence ranged from 0% [ 48 , 49 , 50 ] to 93.4% [ 51 ] across 31 countries. For studies reporting results utilising multiple antigens, both the minimum and maximum were considered for the overall seroprevalence range reported here.…”
Section: Resultsmentioning
confidence: 99%
“…In this scoping review, 94 studies were identified in which authors described the seroprevalence of P. vivax and/or the advantages and disadvantages of their chosen serological method. Seroprevalence was found to vary widely, from 0% [ 48 , 49 , 50 ] to over 90% [ 51 ]. When split by decade, there appears to be no significant difference in seropositivity rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, careful anamnesis on epidemiological risk has to be seriously considered for each donor and recipient in both malaria endemic and non-endemic zones, considering that infection can still be acquired in non-endemic locations including European or American airports or autochthonous malarial foci [ 229 , 230 ].…”
Section: Discussionmentioning
confidence: 99%